Clinimetric properties of the one-leg sit-to-stand test in examining unilateral lower limb muscle strength among young adults - Surachart Thongchoomsin (2020)
© 2020 John Wiley & Sons Ltd Background: One-leg sit-to-stand (one-leg STS) test is a new clinical test developed to measure the unilateral lower limb (LE) muscle strength among young adults. This study examined the test-retest reliability and the criterion-concurrent validity of the one-leg STS. Methods: Forty young adults (mean age ± SD, 28.07 ± 5.39 years) participated in the study. The one-leg STS test was administered in two separate assessment sessions to examine test-retest reliability. Two-leg STS test was administered and the performance time was measured. The concentric peak strength of hip flexors/extensors, knee flexors/extensors and ankle dorsi-flexors/plantar-flexors were determined using an isokinetic dynamometer. An intraclass correlation coefficient (ICC) was used to examine the test-retest reliability of one-leg STS test. The criterion validity of the one-leg STS test was evaluated against the performance of the two-leg STS test using an independent sample t test. The concurrent validity of the one-leg STS test was evaluated by investigating the relationships between STS performance time and LE muscle strength using Pearson correlation coefficients. Results: The reliability analysis showed that one-leg STS performance time had excellent test-retest reliability (ICC3,1 = 0.960, P <.001). Also, the one-leg STS performance time was not different between the first and second sessions, t (39) = 0.672, P =.506. The performance time of the one-leg STS test was significantly greater than the two-leg STS test (t (39) = 20.63, P <.001). The performance time of the one-leg STS test significantly correlated with the concentric peak strength of all LE muscles (P <.05). Conclusions: The one-leg STS test demonstrated excellent reliability and criterion-concurrent validity against the two-leg STS and the LE muscle strength. The one-leg STS test was simple to administer and could be beneficial for the assessment of unilateral LE muscle strength of young adults in clinical settings.